Psychometric properties of the Career Adapt-Abilities Scale–Short Form: evidence from Chinese elite athletes - Hu, Jin-Chuan; Su, Ning; Huang, Yanmei; Zou, Yu-Duo; Liu, Hao; Liu, Jing-Dong (Frontiers in Psychology, 2023)
Objectives: The present study aimed to examine the psychometric properties of the Chinese version of the Career Adapt-abilities Scale-Short Form (CAAS-SF) among a sample of Chinese elite athletes.Methods: A sample of Chinese elite athletes (n=770) was invited to participate in this study. Firstly, the factor structure of the Chinese version of the CAAS-SF was examined and six measurement models (CFA, H-CFA, B-CFA, ESEM, H-ESEM and B-ESEM) were constructed and compared.Secondly, the internal consistency reliability of the Chinese version of the CAAS-SF was examined.Finally, structural equation modeling (SEM) was employed to assess the nomological validity of the Chinese version of the CAAS-SF.Results: The results showed that the hierarchical-ESEM (H-ESEM) model best represented the factor structure of the CAAS-SF among Chinese elite athletes. It suggests that the higher order factor of career adaptability explains the four distinctive but inter-related specific factors of concern, control, curiosity and confidence. The Cronbach's alpha coefficients (0.84-0.90), composite reliability (0.81-0.96) and coefficient omega hierarchical (0.855-0.94) of the Chinese version of the CAAS-SF were larger than the cut-off values, which suggest satisfactory reliability. The results of the SEM revealed that the higher-order factor of career adaptability was positively associated with career decision selfefficacy (β = 0.676, p＜0.001). This result is consistent with previous findings (r=0.65, p< 0.01) and provided support for the nomological validity of the CAAS-SF among Chinese elite athletes.The findings of the present study indicated that the Chinese version of the CAAS-SF displayed satisfactory reliability and validity and could be used to assess career adaptability of Chinese elite athletes. In addition, total score of the CAAS-SF is suggested to be used in future research and practical works.